The dependable deep time Acacia: Anthracological analysis from Australia's oldest Western Desert site. (December 2021) - Byrne, Chae; Dotte-Sarout, Emilie; van Leeuwen, Stephen; McDonald, Jo; Veth, Peter
Highlights: Firewood and collection strategies in the Australian Western Desert. Karnatukul (Serpents Glen) Katjarra (Carnarvon Ranges). Anthracological application to rarely applied deep time arid site. Acacia resource essential to habitability of the arid landscape. Abstract: Despite environmental factors being at the forefront of socio-ecological models in Australian archaeology, detailed local environmental and vegetation datasets are uncommon. Such data is important in assessing, for instance, if and how shifting climatic conditions influenced and conditioned hunter-gatherer movements and choices. Archaeological re-excavation of Karnatukul (Serpents Glen) in Katjarra (the Carnarvon Ranges) provided an opportunity to undertake anthracological (archaeological wood macro-charcoal) analysis. This data offers an insight into the earliest uses of firewood and collection strategies in the Australian Western Desert. This study aimed at testing global anthracological methodologies to examine the problems and potentials offered by this important sub-discipline which is currently developing in Australian archaeology. This study makes an important contribution to international anthracological studies, given these are rarely applied to arid contexts, especially with an occupation record spanning almost 50 ka. The study demonstrates the presence and persistence of Acacia ( sens. str. ) woodlands from the Pleistocene, through the Last Glacial Maximum, and into the Holocene with the case made that this productive plant makes an essential contribution to the habitability of this arid landscape.